The Role of School Principals in Promoting Inclusive Schools: A Teachers’ Perspective - Khaleel, Nida; Alhosani, Mohamed; Duyar, Ibrahim (Frontiers in Education, 2021)
After the enactment and implementation of a series of inclusive education policies in the United Arab Emirates (UAE) and worldwide, a number of challenges have hindered the effective implementation of these policies. The current study investigated the conditions of inclusive schools in the context of the UAE and focused on examining the role of school principals in promoting inclusive schools in the city of Al Ain, UAE. A qualitative research design was employed using a phenomenological approach. A semi-structured interview protocol was used to gather data from the participants. A total of 10 special education and general education teachers, 5 from public schools and 5 from private schools, participated in the study. The qualitative data was then refined and analyzed using thematic analysis. The findings demonstrated the key role of principals in creating and promoting inclusive schools when considering the factors that affect the inclusion of students of determination (SODs), referring to students with special needs, and when implementing the effective inclusive practices in schools. Principals’ awareness of inclusive education emerged as a significant factor in creating and promoting inclusive schools. These findings would illuminate the conditions of promoting inclusive schools in the UAE context and increase policymakers’ and practitioners’ awareness of acknowledging principals’ key role in the effective implementation of inclusive schools. The study recommended a systematic provision of professional development targeting the enhancement and improvement of principals’ awareness of inclusive education and schools.